Kepuasan dan Kemudahan Akses Sebagai Pendorong Loyalitas Menonton : Studi Komparatif Televisi dan Streaming Digital Pada Sinetron Beri Cinta Waktu - Siti Musfita Sari; Elok Fauziah; Nurus Saniatur Rohmah; Muhammad Badrut Tamam; Achmad Afand; M Meylfin Afranzha (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
This study aims to analyze the influence of viewing satisfaction and ease of access on viewing loyalty of the soap opera Beri Cinta Waktu, and to examine the role of these two variables in shaping viewer loyalty amidst the media shift from conventional television to digital streaming platforms. This study uses a quantitative approach with a survey method of 74 respondents who are viewers of the soap opera Beri Cinta Waktu in Pasuruan Regency. Data were collected through a structured questionnaire and analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the help of SPSS. The results show that viewing satisfaction and ease of access simultaneously have a significant effect on viewing loyalty. Partially, viewing satisfaction has a positive and significant effect on viewing loyalty, while ease of access has a stronger and more dominant influence. The coefficient of determination value shows that 60.6% of the variation in viewing loyalty can be explained by these two variables. These findings emphasize the importance of a satisfying viewing experience and ease of access in building audience loyalty in the digital media era.